Socio-emotional and monetary employee-organization resource exchanges: Measurement and effects on daily employee functioning. Issue 2 (2nd April 2020) - Tomprou, Maria; Xanthopoulou, Despoina; Vakola, Maria
ABSTRACT: Daily exchanges between employees and their organisation pertain mainly to socio-emotional resources. We investigate how daily employee-organizational resource exchanges relate to daily strain and work-related self-efficacy. We also examine the role of perceived organisational monetary investments on the relationship between daily employee resource investments and outcomes. To do so, we assess the psychometric properties of the Resource Exchange Scale (RES) that we developed for measuring general and daily employee and organisational resource investments (Study 1 and Study 2). Seventy-six health-care employees completed a general survey and a 10-day diary survey twice: at mid-shift and at the end of their shift (Study 3). Analyses supported the validity of the RES. Findings revealed that daily, under-reciprocal exchange related to increased physical symptoms. Mutual high daily resource investments related to greater work-related self-efficacy. The relationship between daily employee resource investments and self-efficacy was positive under conditions of both high and low perceived monetary investments. Lagged analyses showed that the previous day's self-efficacy related positively to employees' next day resource investments. Our findings suggest that socio-emotional resource exchanges matter for daily employee functioning, over and above between-person effects.